HUBUNGAN SIKAP TERHADAP PENGETAHUAN SISWA PADA MATERI SISTEM PERNAPASAN MANUSIA DI KELAS XI IPA SMA NEGERI 3 BINJAI TAHUN PEMBELAJARAN 2017/2018 - Siti Romaisyah; Ashar Hasairin; Veriati Siregar (Universitas Negeri Medan, 2018)
This study aims to determine students’ knowledge, attitudes of students, attitude relationships to students' knowledge and their contribution to the Human Respiratory System material in class XI IPA SMA Negeri 3 Binjai in Academic Year 2017/2018. The population of this study is all students of class XI IPA SMA Negeri 3 Binjai which consisting of five classes amounted to 190 students. The sample of research consisted of two classes namely XI IPA1 and XI IPA4 as many as 75 students and sampling was done by random sampling technique. The type of research is correlational research. The research instrument used is 25 questions of knowledge test and 30 questions of questionnaire. The results showed that students' knowledge on Human Respiratory System material in class XI IPA SMA Negeri 3 Binjai in Academic Year 2017/2018 is in enough category with the average score of 67.15. Students' Attitudes on Human Respiratory System Material in grade XI IPA SMA Negeri 3 Binjai in Academic Year 2017/2018 is in a pretty good category with the average score of 77.96. Attitude relationship to student's knowledge on Human Respiratory System material including high category (r = 0,662). Contribution of attitude to the students knowledge of 43.82% and hypothesis test results show that there is a significant relationship between attitudes toward student knowledge on the Human Respiratory System material.Keywords: knowledge, attitude, human respiratory system